Computer Assisted Language Learning and English Language Teaching in Thailand: Overview - Khamkhien, Attapol (Mediterranean Journal of Social Sciences, 2012)
Currently, computer assisted language learning (CALL) is widely accepted to be a tool which can be used to facilitatethe language learning process, particularly English language teaching (ELT). The use of CALL has provided a powerful mediumfor language learning from both teaching and learning perspectives. However, the integration of CALL programs in languageinstruction requires a certain level of sensitivity and understanding of how to use the programs appropriately. This paper focuseson using CALL in English classrooms in Thailand. It commences with an overview of the development of using computers in theEnglish classroom. Then, advantages and disadvantages of integrating CALL in English instruction are discussed. Next, varioustypes of learning activities that apply computer technology to English learning and instruction in the Thai context are presented.Previous studies on the use and careful integration of CALL, contributing to success of teaching English and facilitating Englishlearning in the Thai context are explored. Pedagogical implications into teaching English with CALL as a tool are suggested.